Effects of acetylsalicylic acid on coagulation tests and haptoglobin concentrations in rabbits with permanent transvenous pacing - I. Uhrikova; P. Scheer; J. Hlozkova; P. Suchy; M. Sepsi (Veterinární Medicína, 2016)
The aim of this study was to evaluate changes in coagulation tests, haptoglobin concentrations and leukocyte counts in rabbits with right-ventricle pacing medicated with acetylsalicylic acid (ASA). Blood was collected from 35 non-anaesthetised males from the jugular vein at baseline, one and two months after pacemaker implantation. Animals were divided into two groups: non-medicated and medicated with ASA. Total leukocyte and platelet counts were measured on an automatic veterinary flow cytometry haematological analyser. Prothrombin time, activated partial thromboplastin time, fibrinogen levels and D-dimers were determined from citrated blood. We found significantly elevated activated partial thromboplastin times and prothrombin times in ASA in comparison to the control group, but not within the ASA group over time. We also observed a decrease in platelet counts in the control group over time, but not in comparison to the ASA group. No significant changes in total leukocyte counts and haptoglobin concentrations were detected. Medication with ASA may alter coagulation profiles in rabbits with permanent transvenous pacing.